Language development in writing through pair-reviews in EFL learning - Besral, Besral; Yustina, Luli Sari; Basit, Abdul (Universitas Syiah Kuala, 2023)
English as a foreign language (EFL) writing is one of the most important skills besides speaking for candidate teachers in the undergraduate English programs at higher institutions. The current study hypothesizes that pair-reviews or collaboration in the teaching and learning process of paragraph writing contributes to students successful language development. The subject of the study was a class (N=28) of third-semester students majoring in English language teaching at the Faculty of Islamic Education and Teacher Training of Universitas Islam Negeri Imam Bonjol in Padang, Indonesia. The students writing skills were developed through exposure to actual writing by introducing paragraph developments. Through the process of planning and writing, they were guided to the use of pair-reviews. After a training period, they were tested for the final exam, in which no review was allowed. The study found that students writing competence as the result of pair-reviews varied depending on the type of paragraphs being developed. The students average score was 73.5 in the illustration type, 78.28 in the comparison type, and 71.96 in the categorization type. In general, students average scores during this pair-review were 74.58. In the post-test, students average score was 79.3, indicating that pair-reviews significantly affect their writing competence. A conclusion was drawn regarding the influence of pair-reviews on their final writing product (post activity). The study further elaborates on the activities during pair-reviews, roles, and the practice of collaboration in Minangkabau culture and traditions in Padang.